Biological control of the chemostat with nonmonotonic response and different removal rates - Alain Rapaport; Jérôme Harmand (Mathematical Biosciences and Engineering)
We show the global stabilization of the chemostat with nonmonotonic growth, adding a new species as a ''biological'' control, in presence ofdifferent removal rates for each species. This result is obtained by an extensionof the Competitive Exclusion Principle in the chemostat, for the case of twospecies with different removal rates and at least one nonmonotonic response.